Análisis a la gestión económica- financiera de la Cooperativa de Ahorro y Crédito CREDIAMIGO Ltda., periodo 2019-2022 - Cuenca Armijos, María Inés (2024)
Financial cooperatives are fundamental in the economic development of a country; their appropriate administration depends on external and internal factors and on the financial diagnosis that allows management to make the right decisions. In this context, the objective of this research is to analyze the economic and financial management of the savings and credit cooperative CREDIAMIGO Ltda., period 2019-2022. The research is descriptive and explanatory with a mixed approach, using deductive, inductive, and analytical-synthetic methods. The main results show that the entity has an adequate financial structure, considering that the total assets are mainly financed with 89.80 % of liabilities and 10.20 % of equity; furthermore, its economic structure is regular; its percentage of expenses is 99.01 % and the profit obtained is equivalent to 0.99 %. With the application of the PEARLS indicators designed by the World Council of Cooperatives, it was determined that the entity under study shows the following aspects: adequate protection, which indicates that the credit risk is being covered; appropriate level of deposits and placements with low delinquency whose result in 2022 is 3.35%, lack of institutional capital because the value obtained is 6.41%, low profitability; as well as slow growth of members, among others. It is concluded that, during the analysis periods, the surpluses are not optimal; however, they constitute a minimal part, as they allow the financial institution to remain in the market.